2021
DOI: 10.1111/hsc.13567
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of effective collaboration among nurse home visitors, healthcare providers and community support services in the United States

Abstract: Collaboration across sectors is needed to improve community health, but little is known about collaborative activities among public health prevention programs. Using the Nurse-Family Partnership® (NFP) home visiting program as context, this qualitative study aimed to describe effective collaboration among nurse home visitors, healthcare providers and community support services to serve families experiencing social and economic adversities. We used grounded theory to characterise collaboration with six purposiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 57 publications
1
12
0
Order By: Relevance
“…We saw generally less collaboration between NFP and providers in housing resources and substance use treatment; though both sectors represent critical needs for some families. Our prior qualitative inquiries have found that NFP nurses rarely share client information with housing service providers 19 . Despite various housing resources available for their clients, the demand for affordable housing far exceeded what was available; limiting opportunities for NFP and housing providers to coordinate.…”
Section: Discussionmentioning
confidence: 99%
“…We saw generally less collaboration between NFP and providers in housing resources and substance use treatment; though both sectors represent critical needs for some families. Our prior qualitative inquiries have found that NFP nurses rarely share client information with housing service providers 19 . Despite various housing resources available for their clients, the demand for affordable housing far exceeded what was available; limiting opportunities for NFP and housing providers to coordinate.…”
Section: Discussionmentioning
confidence: 99%
“…The common denominator for these PHNs was that they worked in smaller places or personally knew people who worked in the collaborating services. Having a contact person in partnering organizations is essential for effective collaboration among home‐visit nurses in public health prevention programmes (Williams et al, 2022). Collaboration with other professions has been emphasized as important and beneficial for detecting vulnerable children and supporting families (Tung et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Strong working relationships between services contribute to effective support for families, with research identifying the need for collaborative communication and practice (Williams et al, 2021). Families with additional challenges often require services beyond the scope of an individual organization, and issues can arise with a lack of alignment in service goals (Tung et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Strong working relationships between services contribute to effective support for families, with research identifying the need for collaborative communication and practice (Williams et al, 2021).…”
Section: Discussionmentioning
confidence: 99%